A Hilbert–Huang transform method for scattering identification in LIGO. (10th November 2017) - Valdes, Guillermo; O'Reilly, Brian; Diaz, Mario
Abstract: Noise produced by light being scattered from objects limited the sensitivity of the laser interferometer gravitational-wave observatory (LIGO) during the observation period O1. This scattering noise followed a defined model relative to the object's motion from which light is being scattered. A method based on the Hilbert–Huang transform was developed to identify the scattering surfaces. In this document, we present the efficiency of our method identifying scattering objects in LIGO.